Effects of the Non-Neutralizing Humanized Monoclonal Anti-Adrenomedullin Antibody Adrecizumab on Hemodynamic and Renal Injury in a Porcine Two-Hit Model. Issue 6 (December 2020) - Thiele, Christoph; Simon, Tim-Philipp; Szymanski, Jeanine; Daniel, Christoph; Golias, Christos; Hartmann, Oliver; Struck, Joachim; Martin, Lukas; Marx, Gernot; Schuerholz, Tobias
Abstract : ABSTRACT: Adrenomedullin is a vasoactive peptide that improves endothelial barrier function in sepsis, but may also cause hypotension and organ failure. Treatment with a non-neutralizing monoclonal anti-adrenomedullin antibody showed improvement in murine sepsis models. We tested the effects of the humanized monoclonal anti-adrenomedullin antibody Adrecizumab in a porcine two-hit model of hemorrhagic and septic shock. In this randomized, blinded study 12 German Landrace pigs were bled to half of baseline mean arterial pressure for 45 min. Sepsis was induced using an Escherichia coli clot placed into the abdominal cavity 6 h after hemorrhagic shock. Animals received either 2 mg/kg BW anti-adrenomedullin antibody or vehicle solution immediately after sepsis induction. After 4 h, resuscitation was initiated using balanced crystalloids and noradrenalin to maintain a central venous pressure of 8 to 12 mm Hg, a mean arterial pressure ≥ 65 mm Hg, and a ScvO2 ≥70% for another 8 h. Hemodynamic parameters, laboratory parameters, and kidney histology were assessed. The amount of volume resuscitation was significantly lower and significantly less animals developed a septic shock in the antibody-treated group, compared with the vehicle group. Kidney histology showed significantly lower granulocytes in both cortex and medulla in antibody-treated animals, while the remaining four kidney measures (serum creatinine and urine output and cortical and medullary injury in histopathology) did not reach the significance levels. After induction of sepsis, plasma adrenomedullin increased immediately in both the groups, but increased quicker and more pronounced in the antibody group. In this two-hit shock model, treatment with an anti-adrenomedullin antibody significantly increased plasma adrenomedullin levels, while significantly less animals developed septic shock and renal granulocyte extravasation was significantly reduced. Thus, therapy with Adrecizumab may provide benefit in sepsis, and clinical investigation of this drug candidate is warranted.